Factors Affecting the Consumers’ Choices of Toothpaste in Jaffna, Sri Lanka - Sathana, V. (JUICE- 2012 University of Jaffna, 2012)
Dynamic business environment is highly competitive and rapidly changing. Rivals supply creates more confusion for the selection of suitable product for the consumers. Marketing mixes and many factors usually create a meaningful difference in a brand’s performance. The objectives of this paper were to identify the important factors influencing on consumer choices and to measure the effect of the factors on consumer choice of toothpaste. Responses were collected from 100 customers from four major food cities in the Jaffna. Convenient sampling technique was used in selecting the customers. To draw the valid conclusion and test them empirically, an exhaustive use of statistical technique of Factor Analysis was made. To further determine the reliability of the data, Kaiser-Meyer-olkin (KMO), Bartlett Test of sphericity and Anti-image correlation were determined. The present study attained four factors as customer delight, product excellence, product attractiveness and advertising. This research revealed that customers had more emphasis on the customer delights than other factors. Customer delight was derived from credibility, availability and fit and finish aspect of toothpaste. However, almost next important weight was given to product excellence as quality, variety and value for money. Third important factor was product attractiveness that consists of branding and packaging attributes. Further product awareness was also last influencing factor and all aspect of product was communicated by advertising. Therefore, it can be concluded that the consumer toothpaste choices have highly depended on the adaptability of all the above mentioned factors.
Keywords: Consumer Choice; Customer Delight; Product Attractiveness; Product Performance